Evaluation of the distribution and accumulation of species of Alicyclobacillus in the fruit concentrate processing environment - Steyn, Catharina Elizabeth (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc Food Sc (Food Science))--University of Stellenbosch, 2011.